Phenotypic correlations between milk production and conformation traits in goats - Valencia Posadas, Mauricio; Barboza-Corona, José Eleazar; Ángel-Sahagún, César Andrés; Gutiérrez-Chávez, Abner Josué; Martínez-Jaime, Oscar Alejandro; Montaldo, Hugo Horacio (Acta Universitaria, 2017)
In this work, we use the records from 643 goats in order to evaluate the phenotypic relationships between conformation traits and milk production in goats. Correlations were estimated using data on goats which included fifteen conformation traits and first lactation milk yield adjusted for age, calving month and 305 milking days (MY1). We also compared the average scores for type traits on the goats under study with those on a sample of goats from the United States of America (USA). Correlations between conformation traits and MY1 were estimated and an analysis was performed to evaluate the nonlinear relationships between them. The highest correlations were found between milk production and udder depth (–0.22), stature (0.18) and rear udder side view (0.12) (p < 0.05), non-linear (cubic) effects for stature and strength being significant (p < 0.05). American goats had a better overall conformation than the Mexican ones but results indicated that goats with better body conformation were not the best for milk production.